Analysis of the Impact of Family Card Issuance Policy on Married Couples: Legal, Social, and Economic Implications - Nanda Zulisma Yenni; Azhari Yahya; Muhammad Adli (International Journal of Law and Society, 2025)
The creation of Family Cards for couples resulting from serial marriages is an administrative policy of the government, but this policy raises legal problems. This is because serial marriages are still not officially recognized according to Law Number 1 of 1974 concerning Marriage. This policy is considered not to provide complete legal protection and has the potential to weaken the principle of legality in the Indonesian marriage legal system. This study aims to analyze the background of serial marriages, analyze the policies of the Dukcapil government in providing legal protection for serial marriages, and analyze the policy of issuing family cards for serial marriage couples. The type of research used is normative legal research using legislative, conceptual, and case study approaches. Data is collected through literature research and compiled qualitatively. The results of the study show that serial marriage occurs due to economic, religious, cultural, social, and lack of legal understanding. Many people choose it because it is considered practical, cheap, and religiously legal, even though it is not recognized by the state. Dukcapil can indeed issue Family Cards for serial couples for administrative needs, but that does not make the marriage legally valid. As a result, legal protections for wives and children remain weak, especially related to inheritance, alimony, child recognition, and civil disputes.  The Marriage Law requires registration for marriage to be legal, so the issuance of family cards for serial couples has the potential to cause multiple interpretations and conflicts of legal norms. The suggestions of this research are to improve legal education, simplify marriage registration, strengthen the role of religious/traditional leaders, and expand isbat nikah so that the family rights of serial couples are legally protected.